Redução do intervalo intrajornada por meio de negociação coletiva e a inconstitucionalidade do parágrafo único do artigo 611-B da CLT - Vieira, Samuel José Cassimiro (2019)
This dissertation aims to study the constitutionality of the single paragraph of Article 611-B of the CLT, which deals with the legal nature of the rules on intrajornada interval for purposes of flexibilization of labor rights. It imerses itself in the social, legal and jurisprudential aspects on the resting periods inserted on long journeys and their relation to hygiene, heatlh and safety of the workplace. It is divided into three parts: the first chapter, reviews the relation between the reason of existence of labor law and the need for breaks throughout the work day as a measure of occupational medicine; in the second, it evaluates the phenomenon of labor law flexissecurity; and into the third chapter it estabilishes the importance of resting periods to the protection of the worker from riss inherent to labor, caused by overwork, mental and physical fatigue. The research assumes an exploratory nature, using the hypothetico-deductive method of approach, conducting the analysis of the doctrine and jurisprudence of the labor tribunals. In the end, it was concluded that the single paragraph of Article 611-B of CLT is unconstitucional, since it is not possible to dissociate norms on resting períods from the nature of health, safety and hygiene standards without prior atention to the principles of prevention and precaution.